KEMAMPUAN MEMBACA MEMAHAMI TEKS BAHASA MANDARIN SISWA KELAS VIII SMP FRATER MAKASSAR - Intan Naga Ulaweng; Misnawaty Usman; Burhanuddin Burhanuddin (Wen Chuang:Journal of Foreign Language Studies, Linguistics, Education, Literatures, Cultures, and Sinology, 2022)
INTAN MEYLENIA NAGA-ULAWENG, 2021, "The 8th Frater Junior High School Chinese Text Reading Ability in Makassar". paper. National language education in the Department of Foreign Languages. Language and Writing College. Makassar State University (supervised by Misnawaty Usman and Burhanuddin). The purpose of this research is to obtain data and information about the reading and comprehension of Chinese texts in the eighth grade of Makassar Junior High School. This study is a quantitative descriptive study. The object of this study is the eighth class of Frater Junior High School in Makassar City, with a total of eight classes and a total of 248 students. The sample of this study is the eighth grade G class with a total of 29 students. The samples were determined by random sampling method. The results of the study showed that the Chinese reading and comprehension abilities of the eighth Class G students belonged to the general category (75.4%). Keywords: reading comprehension ability, Chinese text